Development of a Bioluminescent Imaging Mouse Model for SARS-CoV-2 Infection Based on a Pseudovirus System - Xi Wu; Nana Fang; Ziteng Liang; Jianhui Nie; Sen Lang; Changfa Fan; Chunnan Liang; Weijin Huang; Youchun Wang (Vaccines, 2023)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), remains widely pandemic around the world. Animal models that are sensitive to the virus are therefore urgently needed to evaluate potential vaccines and antiviral agents; however, SARS-CoV-2 requires biosafety level 3 containment. To overcome this, we developed an animal model using the intranasal administration of SARS-CoV-2 pseudovirus. As the pseudovirus contains the firefly luciferase reporter gene, infected tissues and the viral load could be monitored by in vivo bioluminescent imaging. We used the model to evaluate the protective efficacy of monoclonal antibodies and the tissue tropism of different variants. The model may also be a useful tool for the safe and convenient preliminary evaluation of the protective efficacy of vaccine candidates against SARS-CoV-2, as well as the treatment efficacy of anti-viral drugs.